2021
DOI: 10.1101/2021.03.31.437931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Limiting the priming dose of a SARS CoV-2 vaccine improves virus-specific immunity

Abstract: Since late 2019, SARS-CoV-2 has caused a global pandemic that has infected 128 million people worldwide. Although several vaccine candidates have received emergency use authorization (EUA), there are still a limited number of vaccine doses available. To increase the number of vaccinated individuals, there are ongoing discussions about administering partial vaccine doses, but there is still a paucity of data on how vaccine fractionation affects vaccine-elicited immunity. We performed studies in mice to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Model predictions suggest quantitative differences in neutralizing antibody and cytotoxic T-cell responses stimulated by the vaccine administration by an SD or LD boost 4 to 20 weeks post priming, see Figure 4. Good agreement is observed with [2, 40] in that the immune responses following the adenovirus vaccination show dose-dependency. By Comparing the SD/SD and SD/LD regimens, we find that larger second doses leads to the more stimulated antibodies and cytotoxic T cells.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Model predictions suggest quantitative differences in neutralizing antibody and cytotoxic T-cell responses stimulated by the vaccine administration by an SD or LD boost 4 to 20 weeks post priming, see Figure 4. Good agreement is observed with [2, 40] in that the immune responses following the adenovirus vaccination show dose-dependency. By Comparing the SD/SD and SD/LD regimens, we find that larger second doses leads to the more stimulated antibodies and cytotoxic T cells.…”
Section: Resultssupporting
confidence: 81%
“…Model predictions suggest quantitative differences in neutralizing antibody and cytotoxic T-cell responses stimulated by the vaccine administration by an SD or LD boost 4 to 20 weeks post priming, see Figure 4. Good agreement is observed with [2,40] in that the immune responses ≈ 0.6 γ a 0.5 ≤ P RCC < 0.6 α 73 0.8 < P RCC < 0.9 γ v 0.8 < P RCC < 0.9 γ t ≈ 0.7 C (CTL) µ 21 0.6 < P RCC < 0.7 µ 32 0.6 < P RCC < 0.7…”
Section: Antibody and Cytotoxic T-cell Responsessupporting
confidence: 83%
See 1 more Smart Citation
“…Recent studies have explored scenarios for reduced vaccine dose size, to consider if vaccine supply is scarce. In [ 40 ] the authors studied the effects of reducing the prime dose of a SARS-CoV-2 adenovirus-based vaccine in a mouse model. Their in vivo experiments demonstrated that mice initially primed with a low-dose (LD) vaccine significantly exhibited a higher level of the immune response.…”
Section: Discussionmentioning
confidence: 99%